68.3k views
2 votes
So, I'm working on a math assignment and I don't quite get it. Do you think you could help me? Thank you! 8x-4=13x+6​

1 Answer

5 votes

Answer:

x equals 2

Explanation:

Simplifying

8x + 4 = 13x + -6

Reorder the terms:

4 + 8x = 13x + -6

Reorder the terms:

4 + 8x = -6 + 13x

Solving

4 + 8x = -6 + 13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13x' to each side of the equation.

4 + 8x + -13x = -6 + 13x + -13x

Combine like terms: 8x + -13x = -5x

4 + -5x = -6 + 13x + -13x

Combine like terms: 13x + -13x = 0

4 + -5x = -6 + 0

4 + -5x = -6

Add '-4' to each side of the equation.

4 + -4 + -5x = -6 + -4

Combine like terms: 4 + -4 = 0

0 + -5x = -6 + -4

-5x = -6 + -4

Combine like terms: -6 + -4 = -10

-5x = -10

Divide each side by '-5'.

x = 2

Simplifying

x = 2

User Constance
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.